Pengaruh Kompetensi Dan Objektivitas Terhadap Kualitas Audit Aparatur Pengawas Inspektorat Kabupaten Seluma - Trio Novaldi; Karona Cahya Susena; Yun Fitriano (UNIVED Press, 2023)
The number of corruption cases that occurred, one of which was in the local government, therefore the researchers conducted a study that aims to test whether there is an influence of the competence of the supervisory apparatus of the Seluma Regency Inspectorate on audit quality and whether there is an influence of the objectivity of the Seluma Regency Inspectorate's supervisory apparatus on audit quality. This type of research is quantitative, the data collection method uses a survey method by distributing questionnaires that are arranged in writing, structured and systematic, while the data analysis technique uses a research instrument test, multiple linear regression, coefficient of determination and hypothesis testing. The results of this study found that there was an influence between competence and objectivity on audit quality, which can be seen from the results of the regression analysis which showed Y = -4.660 + 0.545 X_1 + 1.285X_2, the coefficient of determination was 0.581, the results of the t-test for competence were 0.004 and objectivity was 0.000, which means that it indicates that competence and objectivity are less than 0.05, meaning that competence and objectivity have a significant effect on audit quality, and supported by the results of the F test which shows a significance value of 0.000 <0.05, meaning that the independent variables are X_1 (competence) and X_2 ( objectivity) has a significant effect simultaneously on audit quality (Y)